STRESS LEVELS FOR PEOPLE WITH DIABETES MELLITUS DURING THE COVID-19 PANDEMIC - Dwi Uswatun Khasanah; Fatchurrozak Himawan; Suparjo Suparjo (Prodi D3 Keperawatan Tegal Poltekkes Kemenkes Semarang, 2021)
Since December 2019, Coronavirus Disease 2019 (COVID-19) which first appeared in Wuhan, China has seen a rapid increase in cases and deaths worldwide, including Indonesia. Several studies have shown that diabetes is one of the most commonly reported co-morbidities in severe COVID-19 patients. This fact causes psychological problems for people with Diabetes Mellitus, one of which is stress. Prolonged stress can lead to poor glycemic control. Therefore, it is necessary to identify stress in people with Diabetes Mellitus. The purpose of the study was to obtain an overview of the stress level of people with Diabetes Mellitus. The design of this study was a quantitative research with a descriptive approach. The number of samples as many as 33 respondents with purposive sampling technique. Stress levels were measured using the Perceived Stress Scale (PSS)-10 questionnaire. The results of the study showed that most of the respondents had moderate stress levels (42.42%). The results of this study can be a reference for nurses in preventing and overcoming stress in people with Diabetes Mellitus.